The Role of Halal Supervisors in Assisting MSMEs in Obtaining Halal Certification at the Jakarta Sharia Quality Audit Institution in 2025 - Murni Parembai (Economics & Islamic Finance Journal (ECIF), 2025)
Halal certification is a crucial instrument for ensuring the halal status of products while strengthening business competitiveness in the global market. However, many Micro, Small, and Medium Enterprises (MSMEs) still face challenges in obtaining halal certification, including administrative challenges, regulatory compliance, and limited resources. The presence of halal supervisors at Halal Inspection Institutions (LPH) is a strategic factor in bridging this gap. This study aims to analyze the role of halal supervisors in assisting MSMEs to obtain halal certification, using a case study of the LPH Quality Syariah. The research approach employed a descriptive qualitative method through in-depth interviews with halal supervisors, MSMEs, and halal auditors. The results indicate that halal supervisors act as educators who improve halal literacy, facilitators in document preparation and administrative requirements fulfillment, mediators between MSMEs and certification institutions, and drivers of halal product competitiveness. This strategic role has resulted in an increase in the number of halal-certified MSMEs and strengthened their readiness to enter the national and global halal industry supply chain. This study emphasizes the importance of strengthening the capacity of halal supervisors and cross-institutional synergy to accelerate the implementation of halal certification in Indonesia.